Molecular Dynamics Study of Self-Assembly of Aqueous Solutions of Poly[9,9-bis(4-Sulfonylbutoxyphenylphenyl) Fluorene-2,7-diyl-2,2'-Bithiophene] (PBS-PF2T) in the Presence of Pentaethylene Glycol Monododecyl Ether (C12E₅) - Stewart, Beverly (2016)
Results are presented using molecular dynamics (MD) of the self-assembly of the conjugated polyelectrolyte poly[9,9-bis(4-sulfonylbutoxyphenylphenyl) fluorene-2,7-diyl-2,2'-bithiophene] (PBS-PF2T) with 680 mM pentaethylene glycol monododecyl ether (C12E₅) in water. Simulations are used to examine the interaction between PBS-PF2T and C12E₅ and suggest a break-up of PBS-PF2T aggregates in solution. These systems are dominated by the formation of cylindrical phases at temperatures between 0 °C and 20 °C and also between 45 °C and 90 °C. More diffuse phases are seen to occur between 20 °C and 45 °C and also above 90 °C. Simulations are related to previous computational and experimental studies on PBS-PF2T aggregation in the presence of tetraethylene glycol monododecyl ether (C12E₄) in bulk and thin films.